The trade-off myth : - Goodstein, Eban (Island Press, 1999)
As the need to confront unplanned growth increases, planners, policymakers, and citizens are scrambling for practical tools and examples of successful and workable approaches. Growth management initiatives are underway in the U.S. at all levels, but many American "success stories" provide only one piece of the puzzle. To find examples of a holistic approach to dealing with sprawl, one must turn to models outside of the United States. In Green Urbanism, Timothy Beatley explains what planners and local officials in the United States can learn from the sustainable city movement in Europe. The book draws from the extensive European experience, examining the progress and policies of twenty-five of the most innovative cities in eleven European countries, which Beatley researched and observed in depth during a year-long stay in the Netherlands.